Direct physiologic assessment of anomalous aortic origin of a coronary artery: Enhanced diagnostics or illusion of insight?. Issue 1 (2nd August 2018) - McElhinney, Doff B.
Key Points: Fractional flow reserve and intravascular ultrasound evaluation are technically feasible in patients with congenitally abnormal coronary arteries arising from the wrong aortic sinus, including those with a slitlike orifice and presumed intramural course. Incorporation of fractional flow reserve and intravascular ultrasound into the evaluation of adults with anomalous coronary artery origins will provide additional data and may be useful in risk assessment, although these data should be interpreted with caution, as the validity of fractional flow reserve findings in this population has not been established. The applicability of fractional flow reserve thresholds for acute coronary syndromes to patients with anomalous coronary artery origins is unknown. Further study will be needed to determine how best to incorporate fractional flow reserve data in the evaluation and management of these patients.